Political connection types and investors’ perceived risk : evidence from Malaysia - Mas Nordiana Rusli; Norman Mohd. Saleh; Hafizuddin-Syah B.A.M.; Mohamat Sabri Hassan (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examines the pervasive political influence in Malaysian businesses, specifically the investors’ perceived risk of political connection. A sample of 312 firm-year observations between 2014 to 2017 reveals that politically connected Malaysian firms are less likely to be perceived as risky compared with their non-connected peers. In particular, reduction of systematic risk in cost of equity as a proxy to perceived risk is more significant for firms connected through directorship because political figures effectively channel substantial benefits in connecting firms under his/her political power. The link between types of political connections and investors’ perceived risk provides a new insight and direction for research about governance factors that affect firm risks.